Exploring an in-store customer journey for customers shopping for outdoor apparel. (November 2021) - Terblanche, Nic S.; Kidd, Martin
Abstract: The omni-channel shopping phenomenon creates major challenges for brick-and-mortar stores to remain relevant and appeal to customers. A way to counteract these challenges is to offer customers a journey where in-store experiences enable them to encounter numerous physical and virtual touchpoints evoked by affective, cognitive, physical, relational, sensorial and symbolic responses. This study ascertained the customer journey activated by the experiences causing value and resulting in intentions to revisit a retailer specializing in outdoor apparel. Our web-based survey collected 300 valid responses for analyses. The statistical analyses confirmed a positive relationship between the customer in-shop experience factors and the shopping trip value experienced, which in turn mediated the relationship with intention to repatronage. Some conclusions are made and various suggestions for future research are recommended.